Social media rules of engagement : why your online narrative is the best weapon during a crisis - Matejic, Nicole (John Wiley and Sons Australia, Ltd, 2015)
Avoid becoming a #PRFail with a solid social media strategy Social Media Rules of Engagement guides you in the development of a bullet-proof social media strategy. You can manage any crisis effectively by having a plan before you actually need one-and by understanding and influencing your audience with military precision. This original, engaging, and informative text with case studies from the coalface offers you the tools you need to avoid scandal and media crises, and to learn how to leverage social media, big data, and influence in your communications strategies. Social media has establi.